Psychological variables related to corruption: a systematic review - Martín Julián; Bonavia, Tomás (Anales de Psicología / Annals of Psychology, 2020)
Nowadays, corruption is one of the most important psychological, social, economic and political issues worldwide. The present paper aims to analyse psychological variables related to corruption through a systematic review of publications from 2008 to 2018. After carrying out a bibliographic search in scientific databases such as Psycinfo, Web of Science and Dialnet, 41 papers were found to match selection criteria. Core topics haven been organizational ethics, cultural beliefs and values, perceived norms and moral, and personality and related variables. Overall, results have shown that organizational variables such as leaders’ behaviour and justification strategies are linked to corruption. Meritocratic and materialist values have also been linked to corrupt behaviour, just like perceiving a corrupt environment and social norms. In regard to personality, features such as narcissism and psychopathy are deeply connected with this phenomenon. On the other side, perception of power and gender have a mixed empirical support.